(untitled) (Research, Society and Development, 2021)
The bean culture has potential for grain productivity gains, however, it has not been achieved in the field. The use of inputs as a growth regulator and foliar fertilizers associated with amino acids can contribute to achieving this goal. The aim was to evaluate the influence of the application of foliar fertilizer containing amino acids and the herbicide 2,4-D in underdoses, as a growth regulator, in the culture of carioca beans. The experimental design used was in randomized blocks with 8 treatments and 5 repetitions. The treatments were constituted by the combinations of the application of leaf fertilizer + amino acid and the herbicide 2,4-D in underdoses, in the stages of development V4, V6 and in pre-flowering, respectively. Plant height, height of insertion of the first pod, number of pods per plant, number of grains per pod, mass of grains per plant, number of plants per plot, productivity and mass of one hundred grains were evaluated. The use of foliar fertilizer + amino acid promoted greater plant height and insertion of the first pod, resulting in gains of 8.7% and 9.1% for the number of pods per plant and grain mass per plant, respectively. Grain productivity also surpassed the control, achieving gains of 19.5%, which represents 333,4 kg more grains. The application of 2,4-D resulted in a reduction in plant size, but did not increased grain yield.